Barriers and Factors Affecting Nursing Communication When Providing Patient Care in Jeddah - Ruba M. Alharazi; Rahaf J. Abdulrahim; Alhanouf H. Mazuzah; Reem M. Almutairi; Hayfa Almutary; Aisha Alhofaian (Clinics and Practice)
Background/Objectives: Effective communication between nurses and patients plays a crucial role in the delivery of quality healthcare services, especially when caring for patients from diverse cultural backgrounds. It fosters trust, understanding, and collaboration and contributes to better health outcomes and satisfactory nurse–patient relationships. The aim of the study is to assess the factors and barriers affecting nurses’ communication when providing care for patients from diverse cultural backgrounds in Jeddah, Saudi Arabia. Methods: A cross-sectional quantitative descriptive design is used with an online survey instrument. The study involved registered nurses employed in Jeddah’s hospitals. The study utilized a convenience sample for data collection and used the latest version of the statistical package for the social sciences (SPSS version 21) for data entry and analysis. Results: A study of 367 participants found significant barriers to nurse–patient communication, with a mean score of 2.84 on a three-point scale. Key challenges included language differences between nurses and patients with a mean score of 2.87, and cultural and religious differences with a mean score of 2.83 and 2.81, as well as nurses’ communication skills, attitudes, and self-confidence and patients’ awareness, attitudes, and resistance to communication. The multifaceted nature of these barriers emphasizes the need for targeted interventions to improve nurse–patient interactions and enhance care quality. Conclusions: The study highlights the impact of various factors on effective communication between nurses and patients, emphasizing the need for nurses to develop their communication skills and to receive adequate training from nursing officials.